2021
DOI: 10.1093/nutrit/nuab115
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharides on inflammation, immunomodulation, oxidative stress, and gut immune response: a systematic review

Abstract: Context Evidence shows that fructooligosaccharides (FOSs) can modulate inflammatory, oxidative, and immune activity in the gut, possibly leading to a systemic response, improving human health. Objective To assess the present knowledge of the effects of FOSs on inflammation, immunomodulation, oxidative stress, and gut immune response. Data Sources Studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Hence, especially for the obesity-related OA (mainly manifested as an inflammatory reaction process), which is related to the obesity-related GM dysregulation, and could restore a healthy microbial community via the use of indigestible prebiotic fiber Fructooligosaccharides . Fructooligosaccharides can induce the alterations in the abundance of key microorganisms in obese individuals, decrease the response characteristics of colon macrophages, reduce the systemic and joint inflammation, protect the articular cartilage, and further alleviate the progression of OA ( 146 , 147 ). Thus, more and more evidence has revealed that the supplementation of probiotics and prebiotics could reduce the expression of pro-inflammatory cytokines and cartilage-degrading factors in several joint tissues, enhance the production of anti-inflammatory factors and cartilage matrix synthesis cytokines, so as to inhibit combined inflammation and cartilage destruction, and alleviate the development process of OA.…”
Section: The Strategies For the Prevention Or Treatment Of Osteoarthr...mentioning
confidence: 99%
“…Hence, especially for the obesity-related OA (mainly manifested as an inflammatory reaction process), which is related to the obesity-related GM dysregulation, and could restore a healthy microbial community via the use of indigestible prebiotic fiber Fructooligosaccharides . Fructooligosaccharides can induce the alterations in the abundance of key microorganisms in obese individuals, decrease the response characteristics of colon macrophages, reduce the systemic and joint inflammation, protect the articular cartilage, and further alleviate the progression of OA ( 146 , 147 ). Thus, more and more evidence has revealed that the supplementation of probiotics and prebiotics could reduce the expression of pro-inflammatory cytokines and cartilage-degrading factors in several joint tissues, enhance the production of anti-inflammatory factors and cartilage matrix synthesis cytokines, so as to inhibit combined inflammation and cartilage destruction, and alleviate the development process of OA.…”
Section: The Strategies For the Prevention Or Treatment Of Osteoarthr...mentioning
confidence: 99%
“…Because the structure and composition of HMOs are not easily reproduced on large scale, oligosaccharides with simpler structures have been developed to mimic the health benefits of HMOs, which are named as nondigestible oligosaccharides (NDOs) (Gibson et al., 2017). As shown in Table 1, a range of NDOs have been developed for prebiotic purpose, including the well‐demonstrated fructo‐ and galacto‐oligosaccharides (FOS and GOS) (Ambrogi et al., 2021; Costa et al., 2022; Fischer & Kleinschmidt, 2018; Hughes et al., 2022) and other potential prebiotic candidates, such as xylo‐oligosaccharides (XOS) (Santibanez et al., 2021), manno‐oligosaccharides (Jana et al., 2021), pectic oligosaccharides (Wongkaew et al., 2022), and raffinose family oligosaccharides (Elango et al., 2022; Stadnicka et al., 2020). These oligosaccharides vary significantly in monosaccharide units, degree of polymerization (DP), and glycosidic linkages; therefore, their non‐digestibility, selective fermentability, and potential health benefits can be quite different.…”
Section: Introductionmentioning
confidence: 99%
“…So far, FOS have shown good effects in many animal and human models. For example, it has been demonstrated that FOS can selectively promote the growth of beneficial bacteria such as Bifidobacterium and Lactobacillus in the intestinal tract (9) and also reduce the production of pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6, and interferon (IFN)-γ to regulate intestinal immunity (10). In addition, FOS can also prevent oxidation and enable blood glucose homeostasis (11, 12).…”
Section: Introductionmentioning
confidence: 99%